Tailor-Made Functional Polymethacrylates with Dual Characteristics of Self-Healing and Shape-Memory Based on Dynamic Covalent Chemistry - Mondal, Prantik; Behera, Prasanta K.; Voit, Brigitte; Boehme, Frank; Singha, Nikhil K. (Macromolecular Materials and Engineering, 2020)
New shape memory polymers with self-healing behavior are obtained by thermoreversible Diels–Alder (DA) cross-linking of a furfuryl group-containing star-block copolymer with 1,1′-(methylenedi-4,1-phenylene)bismaleimide. The star-block copolymer consisting of a 3-arm polycaprolactone (PCL) core and a polyfurfuryl methacrylate shell is synthesized by reversible addition–fragmentation chain transfer (RAFT) polymerization. For this, a 3-arm macro-RAFT agent based on PCL is converted with an appropriate amount of furfuryl methacrylate in the presence of a radical initiator. Films of the DA network are partly insoluble at ambient temperatures. After annealing at 120 °C the films become completely soluble because of the progressing retro-DA reaction. Evaporation of the solvent and subsequent annealing at 60 °C restores the original insoluble state of the material. By means of a scratch test and tensile tests on cut and subsequently mended samples it is shown that the retro-DA reaction facilitates self-healing. Additionally, the films show pronounced shape memory effects with reasonable shape recovery and fixity ratios, which are attributed to the melting and crystallization of the PCL phase.
CRIS-Team Scopus Importer:2022-04-14
Keywords: polymethacrylate; recyclable materials; self-healing materials; shape-memory; “click” chemistry